Um estudo em estratégias de compreensão leitora num curso de letras - Sossai, Martha Angélica (2009)
The present paper intends to analyze about reading comprehension s strategies that students used to practice before, during and after reading. It was realized through questionnaire and a structured interview, both were applied by direct contact. The aim of our study was to know and to study the student s testimony about reading comprehension s strategies applied in texts wrote on teaching and learning process. On this search, newcomers and conclusives students of Language Arts course from private College on São Paulo inland were interviewed based on the perspective of interactive reading. For this study, we observed, described and analyzed the student s testimony about reading comprehension s strategies with goal to know and to help the teacher practice on Higher Education. The population research was formed by forty-five Language Arts students, twenty newcomers and twenty-five conclusive students registered in 2008 on the L.A. course. With this paper we concluded that metacognitive reading strategies can be a way to solve the reading comprehension problem in Higher Education. We concluded with this study that the metacognitive reading strategies can be a path to the problem solve of reading comprehension in Higher Education